Trajectories: digital/visual data on the move. Issue 4 (1st October 2016) - Gómez Cruz, Edgar
Abstract : This article presents an outline of the concept 'Trajectory'. I propose to understand trajectory not only as a trace of movement in a path but also as a working concept to reflect on the possibilities of visual/digital data collection for ethnographic research on the move. Images, I argue, along with some digital affordances such as metadata and GPS, can be a powerful device for ethnographic enquiry and a useful tool for reflexivity if used by making sense of the randomness of everyday mobility. The concept of 'Trajectory' seeks to reflect on the relationship between four elements: mobility, visual data, digital methods and reflexivity, focusing on the use of the mobile phone as a tool to engage with these elements while reflecting on them. The concept of trajectories is intended to establish a dialogue with that of the flâneur in de Certeau's and Benjamin's work and with some current approaches to visual/digital ethnography, especially those related to movement and senses, art and ethnography and mobilities and locative media.